Efficacy of Sedation by Midazolam in Association With Meperidine or Fentanyl and Role of Patient Distress During Elective Colonoscopy. (May 2020) - Pontone, Stefano; Palma, Rossella; Donato, Giuseppe; Borghini, Raffaele; Frattaroli, Stefano; Raniolo, Marilena; Panetta, Cristina; Lauriola, Marco
Abstract : Meperidine and fentanyl are opioids currently used in addition to midazolam for sedation and analgesia during colonoscopy in Italy. The aim of the study was to assess the impact of patients' psychological state before elective colonoscopy on the efficacy of the sedation regimens. Eighty outpatients who underwent an elective colonoscopy were included in our study. The Hospital Anxiety and Depression Scale questionnaire was self-administered to evaluate basal anxiety and depression state. The rate of baseline discomfort was evaluated by a standard 100-mm visual analog scale. Sedation was obtained alternatively with a midazolam–meperidine or midazolam–fentanyl combination. There were no statistically significant differences between the fentanyl and meperidine groups on body mass index, age, and gender composition. Patients in the meperidine group reported less pain during colonoscopy than patients in the fentanyl group. There were statistically significant positive correlations in the meperidine group with the distress, anxiety, and depression. Our study has pointed out greater effectiveness of the midazolam plus meperidine regimen, equal recovery times, and no significant differences in the duration of the endoscopic examinations. The evaluation of patients' psychological status seems to predict the efficacy of sedation when the nociceptive component of pain is well controlled.